1994
DOI: 10.1073/pnas.91.2.629
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for RNA editing in mitochondria of all major groups of land plants except the Bryophyta.

Abstract: RNA editing has been documented in mitochondria of higher plants, notably dicots and monocots. To determine the distribution of mitochondrial RNA editing in the plant kingdom, we have now undertaken a survey of evolutionarily distant plants. RNA editing occurs in all major groups of land plants except the Bryophyta, suggesting that this process is an ancient trait that was established before the radiation of kormophyte plants. No editing is observed in representatives of the green algae, suggesting that editin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 27 publications
2
65
0
Order By: Relevance
“…Likewise, the type of mitochondrial mRNA editing recently described in dinoflagellate mitochondria (41) has not been found in the apicomplexans, the evolutionary sister group of dinoflagellates, nor in the ciliates, which together with apicomplexans and dinoflagellates constitute the Alveolata (40). The editing observed in plant organelles (C-to-U and U-to-C) does not seem to extend beyond the land plants, as no evidence of this type of editing has been found in any of the green algal mitochondrial systems so far examined, including the charophyte algae (26,52,53), the specific sister taxon that forms a monophyletic group (Streptophyta) with land plants.…”
Section: Mitochondrial Rna Editing Systems Are Phylogenetically Isolatedmentioning
confidence: 95%
“…Likewise, the type of mitochondrial mRNA editing recently described in dinoflagellate mitochondria (41) has not been found in the apicomplexans, the evolutionary sister group of dinoflagellates, nor in the ciliates, which together with apicomplexans and dinoflagellates constitute the Alveolata (40). The editing observed in plant organelles (C-to-U and U-to-C) does not seem to extend beyond the land plants, as no evidence of this type of editing has been found in any of the green algal mitochondrial systems so far examined, including the charophyte algae (26,52,53), the specific sister taxon that forms a monophyletic group (Streptophyta) with land plants.…”
Section: Mitochondrial Rna Editing Systems Are Phylogenetically Isolatedmentioning
confidence: 95%
“…In evolutionary terms, this process is significant as it masks the deleterious effect of a T-to-C mutation by editing C for U after transcription, thus enabling a gene carrying this point mutation to retain its functionality. This type of editing was once considered to have developed with the emergence of tracheophyte (vascular plants) during land plant evolution (Oda et al, 1992;Hiesel et al, 1994). A later editing study of the mt cox3 gene indicated that the C-to-U editing occurs only rarely in bryophytes, greatly increasing its site in pteridophytes and gymnosperms (Malek et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…RNA-editing events involving the conversions of cytidines to uridines and uridines to cytidines have been observed in the mitochondria of angiosperms and basal land plants (Hiesel et al, 1994;Maier et al, 1996;Malek et al, 1996;Sper-Whitis et al, 1996;GiegĂ© and Brennicke, 1999;Steinhauser et al, 1999) but appear to be absent in the subclass of complex thalloid liverworts (Marchantiidae) ) and the few algae examined to date, including Mesostigma, Chaetosphaeridium (Turmel et al, 2002c), and members of the Charales (Malek et al, 1996;Steinhauser et al, 1999). This phylogenetic distribution supports the idea that RNA editing was acquired by streptophyte mitochondria coincidentally with the emergence of land plants but was lost secondarily or extremely reduced in incidence in the Marchantiidae .…”
Section: Introductionmentioning
confidence: 99%